2020
DOI: 10.3390/ijerph17072338
|View full text |Cite
|
Sign up to set email alerts
|

How Teachers Deal with Cases of Bullying at School: What Victims Say

Abstract: Student victims of peer bullying (n = 223) in 25 coeducational Australian schools answered a questionnaire to provide accounts of how their school responded to their requests for help. In addition, respondents indicated how severely they were emotionally impacted by the bullying and whether the bullying was perpetrated by an individual or by a group. The reported outcomes from the intervention indicated that in 67% of cases the bullying stopped or was reduced. In cases where the emotional impact was reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
1
36
0
4
Order By: Relevance
“…pack in Maltese schools that showed a significant reduction in the level of self-reported bullying among severely bullied students [25]. The effectiveness of the intervention for severe victims, even with a small effect size is particularly relevant since previous studies have showed that children with high levels of peer rejection may continue to be victimized after anti-bullying interventions [21], especially when the interventions were delivered by teachers [22]. In addition, our study suggested that it is possible to intervene not only in relation to severe victims [23,24], but to include the whole class in the program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pack in Maltese schools that showed a significant reduction in the level of self-reported bullying among severely bullied students [25]. The effectiveness of the intervention for severe victims, even with a small effect size is particularly relevant since previous studies have showed that children with high levels of peer rejection may continue to be victimized after anti-bullying interventions [21], especially when the interventions were delivered by teachers [22]. In addition, our study suggested that it is possible to intervene not only in relation to severe victims [23,24], but to include the whole class in the program.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kaufman and colleagues [21] pointed out that even if universal anti-bullying interventions can produce effective results, some children with high levels of peer rejection and individual risk factors (e.g., internalizing and parent-child relationship problems) continue to be victimized. In addition, Rigby [22] stressed that when bullying is particularly severe, teacher-led interventions were less successful.…”
Section: Effectiveness Of Anti-bullying Interventions On Victimsmentioning
confidence: 99%
“…We also found that in the case of teachers it is more likely that they approve the non-confrontative interventions, such as discussions with the actors involved with a view to improve the situation or to cooperate/communicate with the family representatives and do not greatly favor the authority-based measures, which are mostly mentioned by the majority of the pupils (imposing discipline through grounding or harsher penalty). Teachers' resilience to active involvement in bullying situations is also mentioned in findings from other studies, where it is stated that, in general, teachers who become aware of bullying incidents choose to take measures rather than to ignore the situation (Rigby et al 2020).…”
Section: Suggested Measures At the Family Levelmentioning
confidence: 83%
“…However, some feel sorry for the victim and try to ease the situation in their capacity (Rigby, 1997). Studies have also shown that victims seldom seek help from their teachers or parents; they think intervention from teachers or parents is ineffective and only brings in more harassment from the bullies (D Olweus & Gredler, 1993;Rigby, 2020b). Literature Review School management is responsible for promptly addressing any reported bullying cases within their schools and should have defined policies and procedures compliant with the school's culture.…”
Section: ___________________________________________________________________________mentioning
confidence: 99%